Effect of metabolism cage housing on rodent welfare - Tarland, Emilia (2007)
The metabolic cage is developed to be able to have a control of total intake of feed and water and the excretion with urine and faeces. In addition, one can efficiently collect non contaminated samples of urine and faeces. For the animal, housing in a metabolic cage involves isolation and problems with cage enrichment since that can interfere with the total collection of urine and faeces. However little research has been done to investigate possible welfare problems for rodents placed in metabolic cages. Housing rodents socially isolated may lead to elevated corticosterone levels and more vulnerability to stress compared to group housed individuals. Studies have also found changes in the central nervous system and the immune system in individually housed rodents. Several negative effects of housing on grid floor are documented e.g. lesions and nerve injury in the hind feet of rats, elevated blood pressure, heart rate and body temperature. Especially mice show a strong preference for nesting material and lack of such may be stressful. More research on the effects of metabolism cage housing on rodent welfare are needed to develop a metabolic cage which enables sampling of uncontaminated urine while allowing the animals to perform their natural behaviours.